"Doing gender" in critical event studies: a dual agenda for research. Issue 1 (1st December 2020) - Dashper, Katherine; Finkel, Rebecca
Abstract : Purpose: To introduce critical gender theory to events studies and set an agenda for research in this area. This paper focuses on various contexts, approaches and applications for "doing gender" in critical event studies. It draws upon interdisciplinary frameworks to develop robust theoretical ways of interrogating issues related to power and structural inequalities in events contexts. Design/methodology/approach: A conceptual discussion of "doing gender" and critical gender theory and review of relevant research in this area within event studies. Adopting feminist and intersectional perspectives and applying them to events environments has potential to inform current theoretical developments and wider sector practices, and, ultimately, change the dominant heteronormative patriarchal paradigm of the experiential landscape. Findings: Event studies has been slow to engage with gender theory and gender-aware research, to the detriment of theoretical and practical development within the field. Research limitations/implications: A call for more gender-aware research within event studies. The goal of this paper is to galvanise gender-aware events research to centralise the marginalised and amplify feminist voices in critical event studies. Feminist and gender-aware frameworks encourage researchers to be critical and to question the underlying power structures and discourses that shape practices, behaviours and interactions. This creates new pathways to find ways to overcome inequalities, which can improve overall events praxis. Originality/value: The paper introduces critical gender theory as a fruitful framework for future events research. It is an under-researched area of study, representing a significant gap in ways of theorising and representing different aspects of events. We argue it is imperative that researchers take up the challenge of incorporating feminist and/or gender-aware frameworks within their research as a matter of routine.